Incorporação de elementos-traço em Loricariidae (Teleostei: Siluriformes) em córregos na bacia hidrográfica do rio Sucuriú, Centro-Oeste do Brasil - MARTHA DA ROCHA PEREIRA (2025)
Commonly known as "heavy metals," trace elements are chemical compounds naturally available in different environments. Trace elements can be classified according to their physiological and metabolic importance into essential and non-essential categories. However, even essential trace elements, which have physiological and metabolic pathways, can become highly toxic at elevated concentrations, similar to non-essential elements. Thus, the growing concern of the scientific community about the intensification of trace elements arises from numerous risks they pose to aquatic communities, which are directly or indirectly affected. In this context, the present dissertation aims to evaluate the presence of Zn and Cd in Cerrado streams and investigate whether these elements accumulate in Loricariidae species. Furthermore, it seeks to assess the efficiency of using Loricariidae species in trace elements monitoring. To achieve this, we sampled liver and muscle tissues from five Loricariidae species and, alongside water samples, quantified the concentrations of Zn and Cd using spectrophotometric methods. In the water samples, Zn and Cd concentrations were found to exceed the limits established by Brazilian legislation (0.18 mg L-1 and 0.001 mg L -1, respectively). We also detected Zn and Cd in five of Loricariidae species collected. A trend was observed in which Zn accumulated predominantly in the liver, while Cd accumulated more significantly in the muscle tissue of the animals. Although all Loricariidae species studied demonstrated potential as bioindicators of trace element contamination, we recommend the use of Hypostomus ancistroides and H. nigromaculatus as model organisms due to their broader distribution throughout the hydrographic basin. In summary, the findings of this dissertation highlight potential contamination of streams in the Sucuriú River hydrographic basin, which, over time, could compromise populations, particularly those positioned at higher trophic levels, including humans.